Nanoparticle-based radiosensitization strategies for improving radiation therapy - Shen, Hongxin; Huang, Hong; Jiang, Zhimei (Frontiers in Pharmacology, 2023)
Radiotherapy remains the mainstay treatment for a variety of cancer forms. However, the therapeutic efficiency of radiation is significantly limited by several aspects, including high radiation resistance caused by low reactive oxygen species concentrations and a low absorption rate of radiation by tumor tissue, inappropriate tumor cell cycle and tumor cell apoptosis, and serious radiation damage to normal cells. In recent years, nanoparticles have been widely used as radiosensitizers due to their unique physicochemical properties and multifunctionalities for potentially enhancing radiation therapy efficacy. In this study, we systematically reviewed several nanoparticle-based radiosensitization strategies for radiation therapy use, including designing nanoparticles that upregulate the levels of reactive oxygen species, designing nanoparticles that enhance the radiation dose deposit, designing chemical drug-loaded nanoparticles for enhancing cancer cell sensitivity to radiation, designing antisense oligonucleotide gene-loaded nanoparticles, and designing nanoparticles using a unique radiation-activable property. The current challenges and opportunities for nanoparticle-based radiosensitizers are also discussed.